Size distribution and estimated optical properties of carbonate, water soluble organic carbon, and sulfate in aerosols at a remote high altitude site in western China - Li, S. M.; J. Tang; Xue, HS; Toom-Sauntry, D. (GEOPHYSICAL RESEARCH LETTERS, 2000)
Measurements at the GAW station in western China reveal the levels and size distributions of chemical components in aerosols. The results indicate similarly high levels of three components, water-soluble organic carbon (WSOC), Ca2++CO3= and NH4++SO4=. Both WSOC and SO4= show a dominant accumulation mode, with a geometric mean mode diameter D-g of 0.41 and 0.34 mu m and geometric standard deviation sigma(sg) of 0.31 and 0.33, respectively. This mode makes up >70% of the total mass of both species. In comparison, Ca2+ and CO3= show a prominent coarse mode with D-g of 2.98 and 1.76 mu m and sigma(sg) of 0.29 and 0.22, respectively, that accounts for >60% of the mass. Based on these characteristics, estimates of the volume scatter coefficient beta, direct back scatter coefficient beta(pi) and mass scattering efficiency phi for each component were made, assuming external mixing and optical and growth characteristics of corresponding pure chemical compounds. The results show that NH4++SO4= has the largest beta, beta(pi) and phi (median 1760x10(-8) m(-1), 79x10(-8) m(-1) sr(-1), and 6.9 m(2) g(-1), respectively). It is followed by WSOC with 1470x10(-8) m(-1), 30x10(-8) m(-1) sr(-1), and 5.3 m(2) g(-1) for beta, beta(pi), and phi, respectively. Ca2++CO3= has only about 10% of the beta and phi values but 20% of the beta(pi) of NH4++SO4= respectively. For both NH4++SO4= and WSOC, the mass scattering efficiency phi is inversely related to their D-g between the size range of 0.2-0.45 mu m.